A calibration method of non-contact R-test for error measurement of industrial robots. (March 2021) - Guo, Yixuan; Song, Bao; Tang, Xiaoqi; Zhou, Xiangdong; Jiang, Zhouxiang
Highlights: A new calibration method for non-contact R-test that extends the measurement range with higher accuracy is developed. The misaligned errors during the process of finding the "top" point of spherical surface are identified and compensated. The viability and effectiveness of the proposed calibration scheme are proved by the experiments. The experimental results show that the designed device can be applied to estimate the robot accuracy. Abstract: This study presents a new calibration scheme for non-contact R-test that extends the measurement range with higher accuracy. First, the structure of the device is redesigned and a new calculation method for obtaining the 3D position of the sphere center is proposed. Then, the error parameters of the sensors' position are optimized and calibrated by the proposed method. The misaligned errors during the process of finding the "top" point of spherical surface are identified and compensated. Compensation experiments indicate that the proposed calibration method reduces the positioning errors at calibration and validation points by at least 80%. The performance of the proposed method is compared to the typical calibration method using the same data. The developed device is applied to measure three types of errors of an industrial robot. Its measurement results are close to the error measured by the laser tracker and the accuracy given by the robot manufacturer.